Research and application of GEP: China’s experience in natural capital accounting - Yang, Haijiang; Gou, Xiaohua; Ma, Weijing; Xue, Bing (Frontiers in Environmental Science, 2023)
In 2013, for raising the awareness of policymakers and researchers on the economic value of ecosystem services, GEP (Gross Ecosystem Product) was proposed by Chinese scholars. As a new attempt at ecosystem services evaluation, GEP has been widely accepted in China and is often used to reveal the effectiveness of regional ecological protection and the relationship between humans and nature. However, there is currently a lack of a systematic review of GEP research. In this study, we found that: (1) GEP can reflect the overall situation of ecological environment and service quality, and help decision-makers and managers formulate and implement sustainable development strategies and ecological protection policies. (2) The contradiction between the depletion of global ecosystem capital and the development of people’s livelihood continues to intensify. About 68.7% of developing countries are facing a “low-low development (low GEP and low GDP)” model. (3) We have constructed the path model of the GEP working system and the path model of ecological protection compensation mechanism in China. The GEP accounting system of “from point to area, from top to bottom”, the parallel evaluation strategy of GDP and GEP and the comprehensive ecological compensation system of “vertical and horizontal combination” implemented can be popularized to countries all over the world.